Managerial support's moderating role in Indonesian lecturers' career insight - Eryanto, Henry; Santoso, Budi; Adha, Maulana Amirul; Susanto, Teguh Trianung Djoko; Eranza, Datu Razali Datu; Ibrahim, Hadziroh; Dwita, Febrisi (Intelektual Pustaka Media Utama, 2024)
Lecturers' academic careers as professional workers have a different process from other workers. Understanding career insights is important for lecturers in carrying out their profession. this research aims to test the moderating effect of managerial support on the influence of career motivation and self-concept on career insight. this research uses quantitative methods, data collection uses instruments with a 1-5 Likert scale. Respondents were 499 lecturers in Jakarta, Indonesia. The data analysis technique uses SEM PLS. The research results show that career motivation and self concept have a positive effect on lecturers' career insight. meanwhile, managerial support does not have a significant moderating effect on the influence of career motivation and self concept on career insight. this research recommends the need for efforts to increase the role of managerial support in increasing lecturers' career insight. this is an opportunity for further research with different theoretical and methodological aspects.